Brown tumor as a result of secondary hyperparathyroidism in chronic renal disease - Mascarenhas, Letícia de Santana; Marchionni, Antonio Márcio Teixeira; Rebouças, Deyvid Silva; Neri, Júlia dos Santos Vianna; Medrado, Alena Ribeiro Alves Peixoto (Journal of Oral Diagnosis, 2016)
Introduction: Brown tumor is a focal lesion of giant cells that develops in association with hyperparathyroidism. Objective: To report a case of brown tumor that occurred in the mandibular symphysis region, associated with secondary hyperparathyroidism. Case report: A 45-year-old male patient with chronic renal failure exhibited increased volume with comorbid local paresthesia in the mandibular symphysis region. Radiographs showed a unilocular radiolucent area with partially defined edges in the anterior mandible region. The histopathological findings revealed connective tissue, rich in oval, notched cells and giant cells with hemosiderin pigments. Laboratory tests showed increased serum levels of parathyroid hormone. An attempt to control the hormone levels with medication while the patient awaited a kidney transplant was unsuccessful. Therefore, as a transplant was not imminent and injury continued to develop, the lesion was surgically excised. Three years later, the lesions recurred in the paranasal region. Following partial removal of the lesions, the patient is now under follow-up care. Conclusion: Correct diagnosis and effective treatment of brown tumor requires correlation of biochemical data with the patient’s clinical, imaging, and histological profile.